Homilies 1-14 on Ezekiel - Origenes 185-254 (Ancient Christian writers, 2010)
General introduction -- Preface of Jerome -- Homily 1: the vision of the prophet (Ezekiel 1:1-6; 2:1ff.) -- Homily 2: against the false prophets (Ezekiel 13:1-19) -- Homily 3: against the false prophets and elders (Ezekiel 13:1, 17-22; 14:1-8) -- Homily 4: the famine and the ferocious beasts (Ezekiel 14:12-22) -- Homily 5: sword, death, vine (Ezekiel 14:13-21; 15:1-4) -- Homily 6: iniquities of Jerusalem (Ezekiel 16:2-16) -- Homily 7: the beneficial effects of God's turning away (Ezekiel 16:16-30) -- Homily 8: brothels, head and base of streets, gifts (Ezekiel 16:30-33) -- Homily 9: iniquities, pride, relative justification (Ezekiel 16:45-52) -- Homily 10: shame, return, restoration (Ezekiel 16:52-63) -- Homily 11: the two eagles, the cedar, the flourishing vine (Ezekiel 17:1-7) -- Homily 12: interpretation (Ezekiel 17:12-24) -- Homily 13: the prince of Tyre, Pharaoh (Ezekiel 28:12-23) -- Homily 14: the closed gate (Ezekiel 44:1-3)